Fe Isotopic Compositions of Modern Seafloor Hydrothermal Systems and Their Influence Factors - Xiaohu Li; Jianqiang Wang; Hao Wang (Journal of Chemistry)
Based on previous research on the Fe isotope compositions of various components and systems of the Earth, this study focused on the Fe isotope compositions of hydrothermal systems, including the Fe isotope variations in chalcopyrite, pyrite, and sphalerite, and their possible controlling factors. The main findings are as follows: (1) The range of Fe isotopes in hydrothermal systems at mid-ocean ridge is very large. The δ56Fe values of hydrothermal fluids are characterized by significant enrichment in light Fe isotopes. (2) The δ56Fe values of sulfides also exhibit lighter Fe isotope characteristics than those of hydrothermal fluids from hydrothermal vent fields at mid-ocean ridge. The vent temperature, fluid properties, and mineral deposition processes significantly affect the δ56Fe values of hydrothermal sulfides. (3) Chalcopyrite is preferentially enriched in heavy Fe isotopes, whereas sphalerite and pyrite are enriched in light Fe isotopes. In addition, the δ56Fe values of pyrite/marcasite display a larger range than those of chalcopyrite. This pattern is directly related to equilibrium fractionation or kinetic fractionation of Fe isotopes during the deposition of sulfides. To better understand the Fe isotope compositions of modern seafloor hydrothermal systems, the geochemical behavior and fractionation mechanisms of Fe isotopes require further in situ study.